1994
DOI: 10.1073/pnas.91.19.9136
|View full text |Cite
|
Sign up to set email alerts
|

BY55 monoclonal antibody delineates within human cord blood and bone marrow lymphocytes distinct cell subsets mediating cytotoxic activity.

Abstract: We had previously reported, using BY55 monoclonal antibody, a cell surface 80-kDa protein restricted to human functional peripheral blood cytotoxic lymphocytes with either natural killer CD3-or cytotoxic T lymphocyte CD3+CD8+ phenotype. In the present report, we studied the cytotoxic lymphocytes in adult bone marrow and newborn cord blood as these organs are commonly used as sources of hematological stem cells for allogeneic transplantation. Our results showed that BYS mAb labeled only 5-10% of the bone marrow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
20
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 25 publications
3
20
0
Order By: Relevance
“…This confirms our initial findings obtained by flow cytometry using the anti-CD160 mAb BY55, which demonstrated that BY55-reactive lymphocytes corresponded to NK cells and to cytotoxic CD8 ϩ T lymphocytes in bone marrow, cord, and PB (18,42). Furthermore, we reported that the intestinal intraepithelial lymphocytes, which spontaneously exhibit a cytotoxic activity, are reactive with BY55 mAb (20).…”
Section: Discussionsupporting
confidence: 89%
“…This confirms our initial findings obtained by flow cytometry using the anti-CD160 mAb BY55, which demonstrated that BY55-reactive lymphocytes corresponded to NK cells and to cytotoxic CD8 ϩ T lymphocytes in bone marrow, cord, and PB (18,42). Furthermore, we reported that the intestinal intraepithelial lymphocytes, which spontaneously exhibit a cytotoxic activity, are reactive with BY55 mAb (20).…”
Section: Discussionsupporting
confidence: 89%
“…Accordingly, Treg cells inhibited the expression of secretion of cytotoxic granules detected by surface expression of CD107 30 (data not shown) and CD160, a marker of circulating highly cytotoxic CD8 ϩ T cells. 31,32 At the same time, the effect of Treg cells on IL-2 expression was not significant in conditions of TCR polyclonal stimulation. Keeping in mind that IL-2 is the predominant cytokine secreted by M CD8 ϩ T cells, in line with their highly proliferative and self-renewing capacity, 5 this result confirmed that Treg cells differentially affect M and E CD8 ϩ T cells.…”
Section: Discussionmentioning
confidence: 63%
“…Further, using the original anti-CD160 mAb BY55 to separate circulating CD160 ϩ NK lymphocytes, we demonstrated that the latter cells corresponded to the effector cytotoxic population (8,9). However, because the BY55 anti-CD160 mAb did not inhibit cytotoxicity of the separated peripheral blood NK (PB-NK) lymphocytes, we were unable to assess whether the structure recognized by BY55 mAb was involved in the target cell recognition (8,9). In the present study, we investigated the function of CD160 expressed on NK cells by using another anti-CD160 mAb, CL1-R2, which inhibits the binding of CD160 receptor to its MHC class I ligands (10).…”
mentioning
confidence: 99%